2021
DOI: 10.1016/j.chemosphere.2020.128716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biodegradation performance and biofouling in a halophilic MBBR-MBR to improve the treatment of disinfected saline wastewater

Abstract: Disinfectant-containing wastewaters have been generated from many places, including marine industries. The synthetic NaClO-containing wastewaters have been effectively treated in a saline MBBR-MBR (moving bed biofilm reactor & membrane bioreactor) system containing marine microorganisms. A low concentration of NaCl (below 100 mg/L) is not enough to kill the microorganisms, but can affect their bioactivity and induce membrane biofouling. A linear relationship has been obtained for the half-life of membrane biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…When the disease is at the beginning stage, the routine blood test is usually unremarkable, so EBV has a high rate of being missed and misdiagnosed. If it is not treated in time, the disease can develop rapidly and even lead to disability or death [ 9 , 10 ]. At present, there is no specific drug for the treatment of IM and symptomatic treatment is often adopted to enhance the autoimmune function of children, and antiviral drug intervention is combined to significantly improve the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…When the disease is at the beginning stage, the routine blood test is usually unremarkable, so EBV has a high rate of being missed and misdiagnosed. If it is not treated in time, the disease can develop rapidly and even lead to disability or death [ 9 , 10 ]. At present, there is no specific drug for the treatment of IM and symptomatic treatment is often adopted to enhance the autoimmune function of children, and antiviral drug intervention is combined to significantly improve the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the operator can also reduce the distance between the needle insertion point and the target nerve by pressurizing the probe so that the operation is simpler. In addition, by tilting the probe to the head side, we could see an oval structure that rose or fell with the respiration, that is, the ultrasound image of the lower pole of the kidney, to prevent the occurrence of adverse events such as kidney puncture [ 18 20 ]. This study showed that there was no statistically significant difference in the incidence of adverse reactions such as local anesthetic poisoning, nausea, vomiting, urinary retention, and pruritus between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that biomaterials with unique (bio)physicochemical properties could mediate cell behaviors and even treat diseases, repair bodily functions, or regenerate tissues [6][7][8][9][10][11][12][13][14][15]. Particularly, the development of nanomaterials and their extensive application in diagnostic/therapeutic biomedicine has received much attention [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%